2013
DOI: 10.1080/09291016.2013.817138
|View full text |Cite
|
Sign up to set email alerts
|

Study on fitness ofDrosophila melanogasterin different light regimes

Abstract: Many aspects of the life cycle in Drosophila are known to be either under circadian control or affected by the circadian clock. The present investigations were made to understand whether changes in the rhythm can affect fitness of Drosophila melanogaster. Fitness such as fecundity, male lifetime fertility, female lifetime fertility, male longevity, and female longevity was assessed in light/dark (LD), continuous light (LL), and continuous dark (DD) for 15th and 30th generations. D. melanogaster showed greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Likewise, in larval and maturing pupal brains, a subset of central circadian clock neuron terminals are in close proximity to the PG neuron dendritic field, and recent studies have shown that PTTH helps coordinate the activity of the central brain clock with the peripheral clock found in the PG (Selcho et al, 2017). This circuit ensures circadian rhythmicity during pupal development, which both influences the timing of pupal development and the observed rhythmicity of adult eclosion that may aid in reproductive success (Kouser et al, 2013). PTTH signaling has also been shown to enhance larval light avoidance at the time of pupation via an E-independent mechanism (Yamanaka et al, 2013a).…”
Section: Discussion Ptth Signaling Is a Nexus For Coordinating Enviromentioning
confidence: 99%
“…Likewise, in larval and maturing pupal brains, a subset of central circadian clock neuron terminals are in close proximity to the PG neuron dendritic field, and recent studies have shown that PTTH helps coordinate the activity of the central brain clock with the peripheral clock found in the PG (Selcho et al, 2017). This circuit ensures circadian rhythmicity during pupal development, which both influences the timing of pupal development and the observed rhythmicity of adult eclosion that may aid in reproductive success (Kouser et al, 2013). PTTH signaling has also been shown to enhance larval light avoidance at the time of pupation via an E-independent mechanism (Yamanaka et al, 2013a).…”
Section: Discussion Ptth Signaling Is a Nexus For Coordinating Enviromentioning
confidence: 99%
“…In fact, the first circadian clock genes were identified in the fruit fly ( Drosophila melanogaster ), and the fruit fly today remains a fundamental model organism for studying genetics, development, and disease (Bellen, Tong, & Tsuda, 2010; Konopka & Benzer, 1971). Constant bright light has been shown to negatively affect fecundity, longevity, and development of D. melanogaster (Kouser, Palaksha., & Shakunthala, 2013; Sheeba, Sharma, Chandrashekaran, & Joshi, 1999). These widespread effects have the potential to alter experimental results utilizing fruit flies.…”
Section: Considerations For Invertebratesmentioning
confidence: 99%
“…Comparatively, few studies have investigated whether fitness in invertebrates is impacted by exposure to dim nighttime lighting ( McLay et al, 2017 ). Previous studies have shown a negative effect of constant light exposure on fecundity and longevity in a model species ( Drosophila melanogaster ) relative to a normal day-night environment ( Kouser et al, 2014 ). Female D. melanogaster chronically exposed to light at night (light intensities of 1, 10 and 100 lx) were less likely to commence oviposition than females exposed to 0 lx light at night ( McLay et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%